The Use of Optical Coherence Tomography to Demonstrate Dark and Light Adaptation in a Live Moth. Issue 4 (28th June 2022) - Berry, Simon
Abstract: To work effectively, the eyes of nocturnal insects have a problem they must overcome. During the night, the light levels are low, so their eyes need to be very sensitive; but they also need a way of adapting to environmental light conditions, and protecting those sensitive organs, if a bright light is encountered. Human eyes have a pupil that changes size to regulate light input to the eye. Moths (Lepidoptera) use a light absorbing pigment that moves position to limit the light within the eye. This pigment migration is difficult to record because it is a dynamic process and will only occur in a live moth. This paper presents the first use of Ocular Coherence Tomography as a method of viewing anatomical detail in a compound eye. This is noninvasive and does not harm the insect. To demonstrate the effectiveness, this article documents the dynamic process of light adaptation within a moth's eye.